Flexible Bandwidth-Based Virtual Network Embedding - Besiktas, Cihangir; Gözüpek, Didem; Ulas, Aydin; Lokman, Erhan; Ozyurt, Ozcan; Ulusoy, Kazim (IEEE, 2016)
Virtual network operators may distrust each other and require that their virtual infrastructure is not cohosted on the same physical equipment. In this paper, we formulate a virtual network embedding problem that maximizes the total revenue where conflicting virtual network operators utilize distinct physical devices. Virtual links in our model have the option of selecting among a range of discrete bandwidth values, which have a corresponding price. This way, any revenue function can be realized. We evaluate the performance of our model by comparing it with a fixed bandwidth scheme and demonstrate its superior performance in terms of revenue.
IEEE/IFIP Network Operations and Management Symposium (NOMS) -- APR 25-29, 2016 -- Istanbul, TURKEY
Keywords: Algorithm